Maternal diet, gestational weight gain, and inflammatory markers during pregnancy. Issue 10 (1st September 2016) - Hrolfsdottir, Laufey; Schalkwijk, Casper G.; Birgisdottir, Bryndis E.; Gunnarsdottir, Ingibjorg; Maslova, Ekaterina; Granström, Charlotta; Strøm, Marin; Olsen, Sjurdur F.; Halldorsson, Thorhallur I.
Abstract : Objective: To examine the associations of gestational weight gain (GWG) and diet with low‐grade inflammation in pregnancy. Methods: A cross‐sectional analysis of 671 pregnant women was performed, and diet was assessed in gestational week 30. GWG was recorded in weeks 30 and ∼37 (difference between the weight recorded at these time points and pre‐pregnancy weight). Markers of inflammation, high‐sensitivity C‐reactive protein (hsCRP), serum amyloid A (SAA), interleukin (IL)−6, IL‐8, IL‐1β, and tumor necrosis factor‐α were quantified in serum from week 30. Results: After adjusting for age, pre‐pregnancy BMI, parity, smoking status, and education, each 1 kg increase in GWG was associated with 3% (95% CI: 1–5) higher hsCRP and 3% (95% CI: 1–4) higher SAA concentrations, which corresponded to ∼18% to 25% increase in these biomarkers among those with excessive weight gain. GWG was inversely associated with IL‐8 while no associations were found for the other inflammatory markers. With respect to diet, women in the highest compared with lowest quintile of protein intake had 26% (95% CI: 3–54) higher hsCRP concentrations. This increase appeared to be driven by intake of animal protein. A similar pattern was observed for SAA. Conclusions: Excessive GWG, as well as high intake of animal protein, was associated with higher concentrations of inflammatory factors.